Misoprostol for miscarriage management in a woman with previous five cesarean deliveries: a case report and literature review - AlSaad D; Al-Obaidly S; Abdulrouf P; Thomas B; Ahmed A; AlHail M (Dove Medical Press, 2017)
Doua AlSaad,1,2 Sawsan Alobaidly,3 Palli Abdulrouf,1 Binny Thomas,4,5 Afif Ahmed,1 Moza AlHail1 1Department of Pharmacy, Women’s Hospital, Hamad Medical Corporation, Doha, Qatar; 2Public Health Program, London School of Hygiene and Tropical Medicine, University of London, UK; 3Department of Obstetrics and Gynecology, Women’s Hospital, 4Clinical Support Service Unit, Hamad Medical Corporation, Doha, Qatar; 5Pharmacy and Life Sciences Research Institute, Robert Gordon University, Aberdeen, Scotland Background: Misoprostol is an effective medical method for the management of pregnancy loss. However, data on its efficacy and safety in women with previous cesarean deliveries are limited.Case presentation: We report a 36-year-old patient, gravida 11 para 6, with a diagnosis of missed miscarriage at 15 weeks of gestation. The patient had a significant obstetric history of previous five cesarean deliveries and uterine rupture. Following patient counseling about the medical and surgical options of managing her miscarriage, the patient opted for medical method. Low-dose misoprostol of 100 µg was inserted vaginally and repeated again after 6 hours. The patient had an uneventful complete miscarriage following the second dose of misoprostol. No uterine rupture, no extra vaginal bleeding, and no blood transfusion were observed.Conclusion: We conclude that adopting a low-dose misoprostol protocol could be potentially safe and effective in managing second trimester missed miscarriage in women with repeated cesarean deliveries and/or uterine rupture history. Further studies are needed to confirm these results. Keywords: cesarean section, uterine rupture, prostaglandin E1, misoprostol, second trimester, miscarriage, abortion